TRPM3 in Brain (Patho)Physiology - Held, Katharina; Tóth, Balázs István (Frontiers in Cell and Developmental Biology, 2021)
Already for centuries, humankind is driven to understand the physiological and pathological mechanisms that occur in our brains. Today, we know that ion channels play an essential role in the regulation of neural processes and control many functions of the central nervous system. Ion channels present a diverse group of membrane-spanning proteins that allow ions to penetrate the insulating cell membrane upon opening of their channel pores. This regulated ion permeation results in different electrical and chemical signals that are necessary to maintain physiological excitatory and inhibitory processes in the brain. Therefore, it is no surprise that disturbances in the functions of cerebral ion channels can result in a plethora of neurological disorders, which present a tremendous health care burden for our current society. The identification of ion channel-related brain disorders also fuel the research into the roles of ion channel proteins in various brain states. In the last decade, mounting evidence has been collected that indicates a pivotal role for transient receptor potential (TRP) ion channels in the development and various physiological functions of the central nervous system. For instance, TRP channels modulate neurite growth, synaptic plasticity and integration, and are required for neuronal survival. Moreover, TRP channels are involved in numerous neurological disorders. TRPM3 belongs to the melastatin subfamily of TRP channels and represents a non-selective cation channel that can be activated by several different stimuli, including the neurosteroid pregnenolone sulfate, osmotic pressures and heat. The channel is best known as a peripheral nociceptive ion channel that participates in heat sensation. However, recent research identifies TRPM3 as an emerging new player in the brain. In this review, we summarize the available data regarding the roles of TRPM3 in the brain, and correlate these data with the neuropathological processes in which this ion channel may be involved.